2021
DOI: 10.1038/s41467-021-21310-4
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-3 is a predictive marker for severity and outcome during SARS-CoV-2 infections

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a worldwide health threat. In a prospective multicentric study, we identify IL-3 as an independent prognostic marker for the outcome during SARS-CoV-2 infections. Specifically, low plasma IL-3 levels is associated with increased severity, viral load, and mortality during SARS-CoV-2 infections. Patients with severe COVID-19 exhibit also reduced circulating plasmacytoid dendritic cells (pDCs) and low plasma IFNα and IFNλ levels when compared to non-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 24 publications
(17 reference statements)
2
41
2
Order By: Relevance
“…Second, patients with severe diseases exhibit reduced circulating pDCs and low plasma IFN-I/λ levels when compared to mild COVID-19 patients 7,19,20 . Third, IL-3, which increases innate immunity likely by promoting the recruitment of circulating pDCs into the airways, is reduced in the plasma of patients with high viral load and severity/mortality 71 . This evidence highlights that several biomarkers of IFN-I/λ response are diminished in COVID-19 patients, and hereby points to pDCs as a primary candidate in the progression of COVID-19.…”
Section: Pdcs Critically Control Viral Replication and The Outcome Of Covid-19 Severitymentioning
confidence: 99%
“…Second, patients with severe diseases exhibit reduced circulating pDCs and low plasma IFN-I/λ levels when compared to mild COVID-19 patients 7,19,20 . Third, IL-3, which increases innate immunity likely by promoting the recruitment of circulating pDCs into the airways, is reduced in the plasma of patients with high viral load and severity/mortality 71 . This evidence highlights that several biomarkers of IFN-I/λ response are diminished in COVID-19 patients, and hereby points to pDCs as a primary candidate in the progression of COVID-19.…”
Section: Pdcs Critically Control Viral Replication and The Outcome Of Covid-19 Severitymentioning
confidence: 99%
“…IL-3 acts as a hematopoietic growth factor. A recent study has confirmed the protective role of IL-3 and its potential use as a predictive marker in severe SARS-CoV-2 infections [ 49 ]. Of note, our data show that IL-3 is indispensable for IFN-γ-induced PD-L1 expression in basophils.…”
Section: Discussionmentioning
confidence: 98%
“…Of note, our data show that IL-3 is indispensable for IFN-γ-induced PD-L1 expression in basophils. Severe COVID-19 patients display low IL-3 in the circulation [ 49 ] that could be responsible for the reduced expression of PD-L1 in basophils reported in one study [ 6 ]. In addition, the reduced IL-3 would also affect the survival of basophils and their ability to support protective IgG responses [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Genetic polymorphisms in all three components of the IL-3 signaling pathway, CSF2RB (coding for the βc Receptor (βcR)), IL-3, and IL- 3 Receptor α (IL-3Rα) genes, are potentially able to directly change gene expressions and have been reported in SCZ ( Chen et al, 2008 ; Chen et al, 2007 ). IL-3 activity may be lower in SCZ patients while impaired IL-3 function is associated with increased disease severity as well as increased viral load and mortality in SARS-CoV-2 infected patients ( Benard et al, 2021 ; Chen et al, 2008 ).…”
Section: β-Common (βC) Cytokines In Scz and Sars-cov-2mentioning
confidence: 99%